Interactions of Chitosan-coated Green Synthesized Silver Nanoparticles using Mentha spicata and Standard Antibiotics against Bacterial Pathogens - Khan, Habib; Andleeb, Saiqa; Nisar, Tayba; Latif, Zahid; Raja, Sadaf A.; Awan, Uzma Azeem; Maqbool, Kiran; Khurshid, Sadia (Current Pharmaceutical Biotechnology, 2023)
Background: Infectious diseases are caused by various multidrug-resistant pathogenic bacteria and in recent scenarios, nanoparticles have been used as innovative antimicrobial agents. Aims: This current research aimed to evaluate the bactericidal effect of chitosan-coated green synthesized silver nanoparticles using aqueous extract of Mentha spicata (MSaqu) against bacterial pathogens, i.e., Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Serratia marcescens, Staphylococcus aureus, and Streptococcus pyogenes. Methods: Synthesis and characterization of silver nanoparticles (MSAgNPs) were carried out via atomic absorption spectrometer and Fourier-transform infrared spectroscopy. Agar well and agar disc diffusion methods were used to assess the antibacterial and synergistic effect of chitosanmediated biogenic silver nanoparticles and standard antibiotics. Three types of interactions, i.e., antagonistic (↓), synergistic (↑), and additive (¥) were observed. Results: Synergistic effect was recorded against Pseudomonas aeruginosa (8.5±0.25 mm↑), Serratia marcescens (19.0±1.0 mm↑), and Klebsiela pneumonia (8.5±0.25 mm↑), an additive effect was exhibited by Escherichia coli (9.0±0.0 mm¥), Streptococcus pyogenes (10.0±0.0 mm¥), and Staphylococcus aureus (7.5±0.25 mm↓) and they showed antagonistic effects when chitosan-coated silver nanoparticles (CLMSAgNPs) were applied compared to chitosan, MSaqu, and MSAgNPs. Interesting antibacterial results were recorded when chitosan-coated Mentha spicata extract and silver nanoparticles were applied along with antibiotics. The synergistic effects of chitosan-coated silver nanoparticles (CLMSAgNPs) + K were recorded against E. coli (14.5±0.25 mm). The synergistic effects of chitosan-coated silver nanoparticles (CLMSAgNPs) + AML were recorded against E. coli (5.5±0.0 mm), S. pyogenes (10.0±0.0 mm), K. pneumonia (5.5±0.0 mm), and S. aureus (4.0±0.0 mm). The synergistic effects of chitosan-coated silver nanoparticles (CLMSAgNPs) + NOR were recorded against E. coli (16.0±0.0 mm), P. aeruginosa (19.0±0.0 mm), S. marcescens (19.5±0.25 mm), S. pyogenes (11.5.0±0.25 mm), K. pneumonia (23.0±0.0 mm), and S. aureus (8.5±0.25 mm). Conclusion: Current findings concluded that chitosan-coated biogenic silver nanoparticles have potential bactericidal effects against infectious pathogens and could be used as forthcoming antibacterial agents.
Keywords: agar well diffusion method